PENGARUH PENERAPAN SIMSKRD TERHADAP KUALITAS LAPORAN KEUANGAN RETRIBUSI IZIN GANGGUAN - Wulandari, Tutut; Hendarsyah, Decky (JURNAL AKUNTANSI DAN INVESTASI, 2020)
This research aims to determine the effect of the implementation of SIMSKRD on the quality of financial reports on permit fees for disturbances in the investment service and one-stop service in Bengkalis Regency at the same time in a descriptive and sharia perspective. The population in this research amounted to 90 people. The sampling technique used in this study was purposive sampling technique so that 30 samples were obtained. The results of this study found that the application of SIMSKRD has been carried out effectively and efficiently and is in accordance with Regional Regulation No. 11 of 2014 and sharia perspective. The quality of nuisance permit financial statements has been said to be relevant, understandable, reliable and comparable and in accordance with sharia perspective. The application of SIMSKRD influences the quality of financial reports on permit fees for disturbances significantly in the investment department and one-stop service of Bengkalis Regency.